Characteristics of Plasma Ring, Surrounding the Earth at Geocentric Distances ~7-10re, and Magnetospheric Current Systems - Stepanova, M (2013)
There are strong experimental evidences of the existence of plasma domain forming a closed plasma ring around the Earth at geocentric distances ~7-10RE. In this work, we analyze the main properties of this ring, using the data of the THEMIS satellite mission, acquired between April 2007 and September 2011. We also analyze the contribution of this ring to the storm dynamics. In particular, it is shown that the distribution of plasma pressure at ~7-10RE is nearly azimuthally symmetric. However, the daytime compression of the magnetic field lines and the shift of the minimal value of the magnetic field to higher latitudes lead to the spreading of the transverse current along field lines and splitting of the daytime integral transverse current into two branches in Z direction. The CRC is the high latitude continuation of the ordinary ring current (RC), generated by plasma pressure gradients, directed to the Earth. We evaluated the contribution of the azimuthally symmetric part of the plasma ring to the Dst index for strong geomagnetic storms using the AMPTE/CCE radial profiles of plasma pressure published before, and showed that the contribution of the ring current including both RC and CRC is sufficient to obtain the observed Dst variation without the necessity to include the tail current system. © 2012 Elsevier Ltd.